2020
DOI: 10.1101/2020.10.02.323584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arabidopsisinositol polyphosphate kinases regulate COP9 signalosome deneddylase functions in phosphate-homeostasis

Abstract: Targeted protein degradation is essential for physiological development and adaptation to stress. Mammalian INOSITOL PENTAKISPHOSPHATE KINASE (IP5K) and INOSITOL HEXAKISPHOSPHATE KINASE 1 (IP6K1) pair modulates functions of Cullin RING Ubiquitin E3 ligases (CRLs) that execute targeted degradation of substrates. Coordinated activities of these kinases protect CRLs on a COP9 signalosome (CSN) platform and stimulates deneddylation-dependent disassembly to maintain continuity of its functions. In plants, CRL regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…In the respective complemented lines ipk1-1:Myc-IPK1 (Walia et al, 2020) or itpk1-2:ITPK1-GFP (Laha et al, 2020), growth defects were abolished and the transgenic plants were indistinguishable to Col-0 (Figure 1a; Figure S1). Further, constitutive expression of phosphate-starvation-inducible (PSI) genes and resulting elevated Pi accumulations previously known for ipk1-1 or itpk1-2 (Kuo et al, 2014;Kuo et al, 2018) were also restored to Col-0 levels in the complemented lines (Figure S2a) (Laha et al, 2020;Walia et al, 2020). Overall, these results validated the corresponding T-DNA mutational consequences on the abnormal growth phenotypes and constitutive PSR in ipk1-1 or itpk1-2.…”
Section: Ipk1 Itpk1 and Vih2 Are Suppressors Of Basal Immunity Agains...mentioning
confidence: 99%
“…In the respective complemented lines ipk1-1:Myc-IPK1 (Walia et al, 2020) or itpk1-2:ITPK1-GFP (Laha et al, 2020), growth defects were abolished and the transgenic plants were indistinguishable to Col-0 (Figure 1a; Figure S1). Further, constitutive expression of phosphate-starvation-inducible (PSI) genes and resulting elevated Pi accumulations previously known for ipk1-1 or itpk1-2 (Kuo et al, 2014;Kuo et al, 2018) were also restored to Col-0 levels in the complemented lines (Figure S2a) (Laha et al, 2020;Walia et al, 2020). Overall, these results validated the corresponding T-DNA mutational consequences on the abnormal growth phenotypes and constitutive PSR in ipk1-1 or itpk1-2.…”
Section: Ipk1 Itpk1 and Vih2 Are Suppressors Of Basal Immunity Agains...mentioning
confidence: 99%
“…In the respective complemented lines ipk1-1:Myc-IPK1 (Walia et al ., 2020) or itpk1-2:ITPK1-GFP (Laha et al ., 2020), growth defects were abolished and the transgenic plants were indistinguishable to Col-0 (Figure 1a; Figure S1). Further, constitutive expression of phosphate-starvation-inducible (PSI) genes and resulting elevated Pi accumulations previously known for ipk1-1 or itpk1-2 (Kuo et al ., 2014; Kuo et al ., 2018) were also restored to Col-0 levels in the complemented lines (Figure S2a) (Laha et al ., 2020; Walia et al ., 2020). Overall, these results validated the corresponding T-DNA mutational consequences on the abnormal growth phenotypes and constitutive PSR in ipk1-1 or itpk1-2 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in phr1 plants this increase was barely detected suggesting that these responses are primarily PHR1-orchestrated. We recently reported that IPK1 and ITPK1 protein stabilities are increased during PSR perhaps signifying their intersection on diverse signaling pathways (Walia et al ., 2020). Likewise, upon PstDC3000 challenge on ipk1-1 : Myc-IPK1 or itpk1-2 : ITPK1-GFP plants we noted improvements in IPK1 and ITPK1 protein stabilities likely reflective of a similar phenomenon (Figure 6f).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations